Development of Structured Inquiries-based Live Workssheet with Chemical Representations to Improve Students’ Higher Order Thinking Skills - Dewi, Suci Firma; Azhar, Minda; Dewata, Indang; Yerimadesi, Yerimadesi; Sovia, Eka; Nofrianto, Nofrianto (Jurnal Pendidikan MIPA, 2022)
Twenty-first century learning means learning designed for millennials to keep up with modern technology. as a result, it requires students to master four learning skills (4Cs), namely: critical thinking, creativity, communication and collaboration. These four skills support students in the learning process now. This study aims uncover the validity, practicality and effectiveness of structured inquiry-based e-modules that use representation to improve student HOTS. The research means research and development (R&D) and the Plomp development model. The query-based E-Module buffer solution is structured and a 3-layer representation is created based on the Plomp development example, which is divided into 3 stages, namely: preliminary research; prototyping; and the assessment stage. The validity test was analyzed using aiken's V derived formula from which validity will occur obtained 0.85 with the category valid. what will happen is that the structured inquiry-based buffer solution module is valid and easy to use for chemical learners. Keywords: e-modules, buffer solutions, live worksheets, multiple representations, structured inquiry DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp792-803